A Revised European Stability Mechanism to Realize Risk Sharing on Public Debts at Market Conditions and Realign Economic Cycles in the Euro Area. (10th May 2018) - Minenna, Marcello; Aversa, Dario
Abstract : In this paper we propose an ambitious reform of the European Stability Mechanism (ESM) to remove two main distortions of the current Eurozone landscape: sovereign yield spreads and large discrepancies in terms of the economic performance. Unlike proposals originated in German or French–German environments which basically pursue risk segregation within peripheral countries, our proposal moves from the recognition that no economic and monetary union can function without sharing risks between the Member States. Hence the idea of turning the European Stability Mechanism into a supranational guarantor of the public debts of all Eurozone governments and reaching—at the end of the transition period—a unique Eurozone federal debt with a unique term structure of interest rates. In return for the savings on the interest expenditure that a similar reform would provide them, risky countries would be required to pay new cash contributions to the ESM capital in the form of marked‐to‐market insurance premiums. This makes the proposal consistent with market logic, matches Germany claims on preventing moral hazard conducts and makes overall more fair and financially sustainable the new ESM set‐up. In addition, the improved capital endowment would allow the Stability Mechanism to keep its moderate leverage unchanged while issuing new liabilities to support high multiplier investments aimed at relaunching peripheral economies and support the re‐alignment of the economic cycles of Eurozone members.